Phylogenomic reappraisal of the family Rhizobiaceae at the genus and species levels, including the description of Ectorhizobium quercum gen. nov., sp. nov. - Ma, Tengfei; Xue, Han; Piao, Chungen; Jiang, Ning; Li, Yong (Frontiers in Microbiology, 2023)
Family Rhizobiaceae contains 19 validly described genera including the rhizobia groups, many of which are important nitrogen-fixing bacteria. Early classification of Rhizobiaceae relied heavily on the poorly resolved 16S rRNA genes and resulted in several taxonomic conflicts. Although several recent studies illustrated the taxonomic status of many members in family Rhizobiaceae, several para-and polyphyletic genera still needed to be elucidated. The rapidly increasing number of genomes in Rhizobiaceae have allowed for a revision of the taxonomic identities of members in Rhizobiaceae. Here, we performed the analyses of genome-based phylogeny and phylogenomic metrics to review the relationships of 155 type strains within family Rhizobiaceae. The UBCG and concatenated protein phylogenetic trees, constructed based on 92 core genes and concatenated alignment of 170 single-copy orthologous proteins, demonstrated that the taxonomic inconsistencies should be assigned to 8 novel genera, and 22 species should be recombined. All these reclassifications were also confirmed by pairwise cpAAI values, which separated genera within family Rhizobiaceae with a demarcation threshold of approximately 86%. In addition, along with the phenotypic and chemotaxonomic analyses, a novel strain BDR2-2 T belonged to a novel genus of family Rhizobiaceae was also confirmed, for which the name Ectorhizobium quercum gen.nov., sp. nov. is proposed. The type strain is BDR2-2 T (=CFCC 16492 T = LMG 31717 T )